2005
DOI: 10.1021/ef0500336
|View full text |Cite
|
Sign up to set email alerts
|

Alkali Metals in Circulating Fluidized Bed Combustion of Biomass and Coal: Measurements and Chemical Equilibrium Analysis

Abstract: Combustion and co-combustion experiments with four kinds of straw, specially selected for their different alkali, Cl, and Si contents, and Columbian black coal were carried out in a circulating fluidized bed (CFB) reactor at Delft University of Technology. The influence of operating conditions and fuel composition on the release of the alkali compounds to the gas phase was investigated. The amount of the total gas-phase sodium and potassium compounds in the flue gases was measured with excimer laser induced fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 66 publications
(47 citation statements)
references
References 20 publications
1
45
0
Order By: Relevance
“…This has also been observed and investigated by other researchers [36,[101][102][103][104]. From the above it can be concluded that silica-containing bed materials should be avoided when operation with "difficult" biomass fuels is intended.…”
Section: Bed Materials and Additives-agglomeration Resistance And Countsupporting
confidence: 62%
See 1 more Smart Citation
“…This has also been observed and investigated by other researchers [36,[101][102][103][104]. From the above it can be concluded that silica-containing bed materials should be avoided when operation with "difficult" biomass fuels is intended.…”
Section: Bed Materials and Additives-agglomeration Resistance And Countsupporting
confidence: 62%
“…These issues, depending on the type of the gasifier, are related to: 3. Operability of the gasifier with fuels containing large amounts of ash, especially if the fraction of alkali, chlorine and sulfur is high [36];…”
Section: Motivation To Apply Gasification As Biomass Conversionmentioning
confidence: 99%
“…The thermodynamic dew points of KOH(g), KCl(g), and K 2 CO 3 (g) for concentrations typically measured in real boilers [23,24] are presented in Fig. 6.…”
Section: Resultsmentioning
confidence: 99%
“…In this calculation, the N 2 (g) partial pressure was still kept at 70 mol% and the change in H 2 O(g) partial pressure effected the CO 2 (g) level accordingly. The potassium and chlorine concentrations were varied between 1 and 100 ppm representing typical levels of these components measured in real boilers at the inlet of the convection section [23,24]. Pressure was fixed in all calculations to 1 atm and the studied temperature range was 400-1000 8C, simulating the temperature range typical in the convection section of a biomass boiler.…”
Section: Calculation Methodsmentioning
confidence: 99%
See 1 more Smart Citation